High-stability electrochromic film as well as preparation method and application thereof
By using quasi-planar heterogeneous interface metal oxides and high-energy ion-assisted electron beam evaporation technology in the electrochromic film, the problem of improving the performance of electrochromic materials in the prior art at the expense of stability is solved, and high stability and ultra-fast switching performance are achieved.
Patent Information
- Application Number
- CN202411977190.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
There is a lot of room for improvement in existing inorganic electrochromic materials to improve response speed and stability, and performance improvement is usually at the expense of stability, making it difficult to take into account both performance and stability.
Quasi-planar heterointerface metal oxide (Q-PHI) is used as the electrochromic layer, and metal oxides are deposited on conductive materials through high-energy ion-assisted electron beam evaporation technology, forming a unique longitudinal gradient distribution characteristic and a powerful built-in electric field.
Significantly improves the overall performance of electrochromic films, including high optical contrast, ultra-fast switching speed and excellent stability, overcoming the trade-off between high stability and fast switching performance.
Smart Images

Figure CN119781220A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochromic thin films, and in particular to a high-stability electrochromic thin film and a preparation method and application thereof. Background Art
[0002] Electrochromism refers to the dynamic adjustment of the visual color and optical properties of electrochromic (EC) materials and devices through electrochemical redox reactions under small external voltage or current stimulation. EC technology has great application potential in various fields, including smart windows for energy-saving buildings, energy-saving displays, and adaptive camouflage systems. At present, various advanced EC materials include organic polymers, inorganic metal oxides, and plasmonic nanomaterials. Among them, inorganic EC materials, such as transition metal oxides such as tungsten oxide and nickel oxide, have gained considerable attention due to their good cost-performance ratio, abundant reserves, and special photothermal stability. However, most inorganic EC materials have inherent brittleness and dense microstructure, which poses a major challenge to the development of EC materials and devices, which strongly restricts their development and wide practical application when combined with ultrafast switching speed, practical durability, and perfect mechanical flexibility. At present, some studies have attempted to improve the performance of WO3 thin films by optimizing the deposition process and interface design. However, the existing technology has not fully utilized the quasi-planar heterointerface design to effectively enhance the electrochromic performance, especially in improving the response speed and stability. There is still a lot of room for improvement.
[0003] To address the above challenges, various strategies are being explored, such as developing nanostructured and / or composite EC materials, optimizing electrolyte ions, and constructing new electrode materials. Low-dimensional nanostructured EC films, including nanodots, nanowires, nanorods, nanosheets, and nanoporous films, can increase the contact area with the electrolyte, shorten the charge transfer distance, reduce internal stress, and significantly improve optical contrast, response time, and flexibility compared to traditional dense films. Although great progress has been made with the help of nanotechnology, these performance improvements are usually achieved at the expense of stability, as the high reactivity induces side reactions and the microstructured fluid degrades during repeated cycles, greatly reducing stability.
[0004] Studies have shown that precisely tuning heterointerfaces in nanostructured EC nanocomposites and planar heterointerfaces on EC / electrolyte interlayers are also effective strategies to improve their comprehensive performance. These works highlight the importance of heterointerface engineering and provide a promising feature to address the inherent limitations of single-phase nanomaterials by creating rich heterointerfaces to generate fast mass and charge transfer. Some artificial solid electrolyte layers on the EC layer / electrolyte heterointerface can also act as buffers, enhancing the elasticity and stability of the film. In contrast, the heterointerface modulation of the electrode / EC layer is often overlooked, which is the site where inhomogeneous electron transfer occurs and the driving force for ion diffusion is generated, which is expected to be closely related to the final EC performance. Some recent reports have demonstrated the above speculation that the performance of EC can be effectively improved by constructing nanostructured interfaces between the electrode and EC layers. For example, self-assembled two-dimensional TiO2 / Mxene heterostructures with well-balanced porosity and connectivity can improve the efficiency of ion and electron transfer in flexible EC devices and have superior mechanical and electrochemical stability (>1000 cycles). Furthermore, porous SnO2 nanosheet scaffolds loaded with multiple active EC materials can significantly improve the cycling durability (>2000 cycles) and light modulation (86% for WO3@SnO2). However, obstacles remain in the large-scale, direct, and reliable controlled construction and integration of nanostructured heterointerfaces with customizable properties, which illustrates the necessity of further enhancing heterointerface design for widespread implementation. Summary of the invention
[0005] The purpose of the present invention is to provide a high-stability electrochromic film and a preparation method and application thereof, so as to solve the problem that the improvement of the performance of the above-mentioned EC materials is usually at the expense of stability, and the performance and stability cannot be improved at the same time.
[0006] To achieve the above objectives, the first aspect of the present invention provides a high-stability electrochromic film, the electrochromic film comprising a conductive material and an electrochromic layer, the electrochromic layer is a quasi-planar heterogeneous interface metal oxide, and the thickness of the electrochromic layer is 10 to 1000 nm.
[0007] Preferably, the metal oxide is one or more of WO3, MoO3, NiO, and TiO2.
[0008] The metal oxides prepared in the present invention are not limited to the above types. Any metal oxide that can be applied to electrochromic thin films can be used to prepare the corresponding quasi-planar heterogeneous interface (Q-PHI) using the preparation method defined in the present invention.
[0009] Preferably, the conductive material includes a substrate and an electrode. The substrate mainly plays a supporting role. The substrate and the electrode can be selected from materials commonly used in the art according to actual needs.
[0010] More preferably, the substrate is one of glass, polyethylene terephthalate (PET), and a metal substrate.
[0011] More preferably, the electrode is one of indium tin oxide electrode (ITO), FTO, and indium cerium oxide.
[0012] A second aspect of the present invention provides a method for preparing a high-stability electrochromic film, comprising the following steps:
[0013] The conductive material is fixed on a sample holder and placed in an electron beam cavity, and the conductive material is pretreated. Then, high-energy ion-assisted electron beam evaporation is used to evaporate and deposit metal oxide on the conductive material to obtain an electrochromic film.
[0014] Preferably, the conductive material in the present invention can be homemade or directly purchased.
[0015] The process of making the conductive material is as follows: ultrasonically clean the substrate with acetone, ethanol, and deionized water in sequence. After cleaning, fix the substrate on the sample holder and place it in the electron beam cavity. Deposit the electrode on the surface of the substrate to form a conductive material. Then, the conductive material can be pretreated without further cleaning. If the conductive material is purchased directly, it needs to be cleaned. The cleaning process is as follows: ultrasonically clean the conductive material with acetone, ethanol, and deionized water in sequence.
[0016] Preferably, the vacuum degree in the electron beam chamber is 1×10 -4 Pa~5×10 -3 Pa, uses high-energy ions to bombard the surface of conductive materials for pretreatment.
[0017] Preferably, the pretreatment time is 1 to 30 minutes.
[0018] Preferably, the metal oxide is heated at 20 to 300°C at a speed of 0.1 to 1 nm·s -1 The rate of evaporation deposition is 200 ℃ and 200 ℃ on the pretreated conductive material.
[0019] Preferably, the high-energy ions are one or more of oxygen ions, argon ions and nitrogen ions.
[0020] Preferably, the acceleration voltage of high energy ions is 130-300V.
[0021] The ion source of high energy ions in the present invention is one of Hall ion source, Kaufman ion source and radio frequency ion source. The processes of preparing and generating high energy ions by Hall ion source, Kaufman ion source and radio frequency ion source are all commonly used in the prior art. Among them, the Hall ion source uses the Hall effect to generate plasma, and accelerates ions in the plasma through an accelerating electric field to generate high energy ions. Its working process is as follows:
[0022] Hall effect: In a Hall ion source, when an electron source (usually a thermal electron source or an electron gun) moves in a strong magnetic field, it is affected by the Lorentz force, causing the electrons to move in a circular motion in the electric field. The electrons collide with gas atoms or molecules to generate ions in the plasma.
[0023] Generation of plasma: The magnetic field and electric field under the Hall effect work together, electrons are accelerated in the electric field and collide with oxygen or argon molecules to produce oxygen ions and / or argon ions and free electrons, thereby forming plasma. The oxygen ions and / or argon ions in these plasmas are accelerated by the electric field to form high-energy oxygen ions and / or argon ions.
[0024] A third aspect of the present invention provides an electrochromic device, which includes the electrochromic film obtained by the above preparation method, an electrolyte layer, a conductive layer and a protective layer.
[0025] In the electrochromic device of the present invention, a gel electrolyte is used as an electrolyte layer, a conductive layer can be one of common electrodes such as ITO and FTO, and a protective layer can be one of common materials such as PET and glass. According to the actual application process, in the preparation process of the electrochromic device, a double-sided adhesive tape can also be used as an adhesive and a gasket, and the edge is sealed with an ultraviolet light-cured adhesive. The thickness of the double-sided adhesive tape is generally 0.5 to 1.2 mm, and more preferably 1 mm.
[0026] Preferably, the electrolyte layer is a gel electrolyte, PMMA and PC are mixed evenly, placed in an oven at 60-80°C for heating and swelling for 15-20 hours to obtain a transparent gel, and then LiClO4 and acetonitrile are added, followed by stirring on a magnetic stirrer at 60-80°C for 10-15 hours to make the electrolyte salt evenly distributed in the transparent gel, thereby finally forming a gel electrolyte.
[0027] Preferably, the molecular weight of PMMA is 100,000 to 150,000, and the mass ratio of PMMA, PC, LiClO4 and acetonitrile is (3 to 5): (8 to 12): (1 to 2): (5 to 10).
[0028] Therefore, the present invention adopts the above-mentioned high-stability electrochromic film and its preparation method and application, which has the following beneficial effects:
[0029] (1) The present invention is different from the traditional planar heterointerface and nanostructured heterointerface. With the help of high-energy ions, it significantly broadens the nanoscale interface contact and unique longitudinal gradient distribution characteristics. The unique quasi-planar heterointerface metal oxide can generate a strong built-in electric field and strong interface bonding, which greatly promotes the transport kinetics of electrons and ions and enhances the Li + The surface adsorption of quasi-planar heterointerface metal oxides was effectively released during continuous electrochemical cycling. Therefore, the electrochromic film formed by the quasi-planar heterointerface metal oxides overcomes the trade-off between high stability and ultrafast switching performance and exhibits remarkable overall EC performance, including high optical contrast, ultrafast switching speed, and excellent stability.
[0030] (2) The present invention can also realize a large-area, flexible EC smart window composed of electrochromic thin films. The invention realizes the preparation of high-performance EC films and devices by constructing quasi-planar heterogeneous interface metal oxides, providing a novel design concept and a simple, effective and scalable strategy.
[0031] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 A schematic diagram of preparing an electrochromic film according to the present invention;
[0033] Figure 2 Surface morphology of ITO in Example 1 and Comparative Example 1;
[0034] Figure 3 The cross-sectional SEM images, ToF-SIMS depth profiles and In + Signal curve amplified from 0 to 1000s;
[0035] Figure 4 The scanning electron microscope cross-sectional views of the electrochromic films in Example 3 and Comparative Example 3 and their transmittance curves in the visible light range (380-780 nm);
[0036] Figure 5 The initial transmission spectrum and color transmission spectrum of the electrochromic film at 380-2500nm in Example 3 and Comparative Example 3, the in-situ transmittance curve under 20s voltage action, the in-situ transmittance curve after 1000 cycles, and the in-situ transmittance curve after 10000 cycles;
[0037] Figure 6 The cross-sectional views of the electrochromic films in Example 2 and Comparative Example 4 are obtained by scanning electron microscope;
[0038] Figure 74 is a cross-sectional view of the electrochromic film in Example 4 and Comparative Example 5 taken by scanning electron microscope;
[0039] Figure 8 The structural diagram of the flexible electrochromic device in Application Example 1, the transmittance curves of the flexible electrochromic device at different driving voltages and digital photos;
[0040] Fig. 9 Schematic diagram of the structure of the electrochromic film;
[0041] Fig.10 is a schematic diagram of the structure of an electrochromic device;
[0042] Fig.11 sectional views of the electrochromic films in Example 6 and Comparative Example 6 taken by scanning electron microscope;
[0043] In the figure: 1. substrate; 2. electrode; 3. electrochromic layer; 4. electrolyte layer; 5. conductive layer; 6. protective layer. DETAILED DESCRIPTION
[0044] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and a specific operation process, but the present invention is not limited to this embodiment.
[0045] Example 1
[0046] The present embodiment provides a high-stability electrochromic film, which includes a substrate, an electrode and an electrochromic layer. The substrate is a transparent substrate and is made of glass. The electrode is a transparent electrode and is made of indium tin oxide. The glass and the indium tin oxide electrode together constitute a transparent conductive material (glass / ITO). The conductive material is directly purchased. The electrochromic layer is a quasi-planar heterogeneous interface tungsten oxide, and the thickness of the electrochromic layer is 40nm.
[0047] Figure 1 It is a schematic diagram of the preparation method of the present invention, and the specific preparation process includes the following steps:
[0048] (1) The transparent conductive material was cleaned with acetone, ethanol, and deionized water for 15 min in sequence, and then dried in an oven at 80°C.
[0049] (2) The cleaned and dried transparent conductive material is fixed on a sample holder and then placed in the electron beam cavity. When the vacuum degree in the cavity reaches 3×10 -3 Pa, the transparent conductive material was pretreated by bombarding the surface of the transparent conductive material with high-energy oxygen ions for 2 minutes. Then, at a temperature of 100°C, Figure 1As shown in the figure, high-energy oxygen ion-assisted electron beam evaporation was used to evaporate tungsten oxide at a speed of 0.35nm·s -1 The rate of evaporation deposition on a transparent conductive material substrate is 40nm, and the electrochromic film (Q-PHI WO3) is obtained. The structure of the electrochromic film is shown in Fig. 9 During the deposition process, the anode voltage for generating high-energy oxygen ions was 150 V, and the oxygen flux was maintained at a rate of 15 sccm.
[0050] The high-energy oxygen ions are generated by a Hall ion source, and the generation process can adopt a preparation method commonly used in the art.
[0051] Example 2
[0052] The present embodiment provides a high-stability electrochromic film, which includes a substrate, an electrode and an electrochromic layer. The substrate is a transparent substrate, which adopts transparent glass, and the electrode is a transparent electrode, which adopts indium tin oxide electrode. The glass and the indium tin oxide electrode together constitute a transparent conductive material (glass / ITO). The conductive material is directly purchased. The electrochromic layer is a quasi-planar heterogeneous interface tungsten oxide, and the thickness of the electrochromic layer is 100nm.
[0053] The specific preparation process includes the following steps:
[0054] (1) The transparent conductive material was cleaned with acetone, ethanol, and deionized water for 15 min in sequence, and then dried in an oven at 80°C.
[0055] (2) The cleaned and dried transparent conductive material is fixed on a sample holder and then placed in the electron beam cavity. When the vacuum degree in the cavity reaches 3×10 -3 Pa, the transparent conductive material was pretreated by bombarding the surface of the transparent conductive material with high-energy argon ions for 2 minutes. Then, at a temperature of 100°C, high-energy argon ion-assisted electron beam evaporation was used to evaporate tungsten oxide at a density of 0.35nms -1 The electrochromic thin film was obtained by evaporation deposition on a transparent conductive material substrate at a rate of 100 nm. During the deposition process, the anode voltage for generating high-energy argon ions was 150 V, and the argon flux was maintained at a rate of 15 sccm.
[0056] High energy argon ions are produced by a Hall ion source.
[0057] Example 3
[0058] The present embodiment provides a high-stability electrochromic film, which includes a substrate, an electrode and an electrochromic layer. The substrate is a transparent substrate and adopts transparent glass. The electrode is a transparent electrode and adopts indium tin oxide electrode. The glass and the indium tin oxide electrode together constitute a transparent conductive material (glass / ITO). The conductive material is directly purchased. The electrochromic layer is a quasi-planar heterogeneous interface tungsten oxide, and the thickness of the electrochromic layer is 200nm.
[0059] The specific preparation process includes the following steps:
[0060] (1) The transparent conductive material was cleaned with acetone, ethanol, and deionized water for 15 min in sequence, and then dried in an oven at 80°C.
[0061] (2) The cleaned and dried transparent conductive material is fixed on a sample holder and then placed in the electron beam cavity. When the vacuum degree in the cavity reaches 1×10 -3 Pa, the transparent conductive material was pretreated by bombarding the surface of the transparent conductive material with high-energy oxygen ions for 2 minutes. Then, at a temperature of 120°C, high-energy oxygen ion-assisted electron beam evaporation was used to evaporate tungsten oxide at a density of 0.35nms -1 The electrochromic film was obtained by evaporation deposition on a transparent conductive material substrate at a rate of 150 V and a deposition thickness of 200 nm. During the deposition process, the anode voltage for generating high-energy oxygen ions was 150 V and the oxygen flux was maintained at a rate of 15 sccm.
[0062] High-energy oxygen ions are generated by a Hall ion source.
[0063] Example 4
[0064] The present embodiment provides a high-stability electrochromic film, which includes a substrate, an electrode and an electrochromic layer. The substrate is a transparent substrate and uses polyethylene terephthalate. The electrode is a transparent electrode and uses an indium tin oxide electrode. The polyethylene terephthalate and the indium tin oxide electrode together constitute a transparent conductive material (PET / ITO). The conductive material is directly purchased. The electrochromic layer is a quasi-planar heterogeneous interface tungsten oxide, and the thickness of the electrochromic layer is 400nm.
[0065] The specific preparation process includes the following steps:
[0066] (1) The transparent conductive material was cleaned by ultrasonic treatment with acetone, ethanol, and deionized water for 15 min in sequence, and then dried in an oven at 80°C.
[0067] (2) The cleaned and dried transparent conductive material is fixed on a sample holder and then placed in the electron beam cavity. When the vacuum degree in the cavity reaches 5×10 -3The transparent conductive material was pretreated by bombarding the surface of the transparent conductive material with high-energy oxygen and argon ions for 2 minutes at 80°C. Then, tungsten oxide was evaporated at a temperature of 0.35nm s -1 The electrochromic film was obtained by evaporation deposition on a transparent conductive material substrate at a rate of 150 V and a deposition thickness of 400 nm. During the deposition process, the anode voltage for generating high-energy oxygen and argon ions was 150 V, the oxygen flux was maintained at a rate of 7.5 sccm, and the argon flux was maintained at a rate of 7.5 sccm.
[0068] High-energy oxygen ions and high-energy argon ions are produced by a Hall ion source.
[0069] Application Example 1
[0070] This application example first adopts the preparation method of Examples 1-4 to deposit a quasi-planar heterointerface tungsten oxide with a thickness of 40 to 400 nm on a transparent conductive material to form an electrochromic film with polyethylene terephthalate (PET) or transparent glass as a transparent substrate, indium tin oxide as a counter electrode, and quasi-planar heterointerface tungsten oxide (Q-PHI WO3) as an electrochromic layer.
[0071] The electrochromic film is applied to a large-area flexible electrochromic device. The electrochromic device uses a gel electrolyte as an electrolyte layer, indium tin oxide as a transparent conductive layer electrode, polyethylene terephthalate or transparent glass as a transparent protective layer, and a 1mm thick double-sided adhesive tape as an adhesive and a gasket. The edge of the electrochromic device is sealed with an ultraviolet light-cured adhesive. The structure of the electrochromic device is shown in Fig.10 .
[0072] Specifically, the electrochromic film (PET / ITO / Q-PHI WO3) prepared in Example 4 was applied, the gel electrolyte was evenly applied to the surface of the PET / ITO / Q-PHI WO3, and double-sided tape was adhered around the PET / ITO / Q-PHI WO3, and then covered with a conductive layer (ITO) and a protective layer (PET), the two film layers were firmly fixed, bubbles were discharged, and the edges of the device were bonded with UV curing glue.
[0073] The preparation method of the gel electrolyte is as follows: 3.5 g of PMMA (M W =120000) and 10g of PC were mixed in a 100mL flask, placed in an oven at 70°C for heating and swelling for 17h, so that the polymer transparent material was well swollen in the polymer swelling agent, and then 1.5g of LiClO4 and 6g of acetonitrile were added to the gel, followed by stirring on a magnetic stirrer at 70°C for 12h, so that the electrolyte salt was evenly distributed in the transparent gel, and finally a transparent gel electrolyte was formed.
[0074] This lightweight and flexible device can achieve dynamic and continuous transparency and color tuning at various driving voltages. Figure 8 As shown, Figure 8 (a) Schematic diagram of the structure of the flexible electrochromic device based on Q-PHI WO3; (b) Transmittance curve and digital photo of the 20 cm × 15 cm flexible electrochromic device based on Q-PHIWO3 at different driving voltages.
[0075] The device was initially highly transparent, with an average transmittance of 79.4% at 400-1000nm. When a voltage of -3.5V was applied to the device, the color changed to light blue, and as the voltage was further increased to -3.8V, the color changed to dark blue. At 1000nm, the maximum optical contrast of the flexible EC device reached 67.6%. The special light modulation performance of the device in the bent state indicates the great application potential of Q-PHI WO3 film in flexible displays, lightweight smart windows and wearable integrated systems.
[0076] Comparative Example 1
[0077] This comparative example is based on Example 1, and adopts the same cleaning steps as Example 1, and is dried in an oven at 80° C. After cleaning, Comparative Example 1 does not undergo high-energy oxygen ion bombardment pretreatment, and the remaining steps are consistent with Example 1.
[0078] The present invention tests the ITO electrode surfaces after pretreatment in Example 1 and Comparative Example 1, respectively, to further illustrate the advantages of the ITO electrode surface after treatment in Example 1. Scanning electron microscopy and atomic force microscopy tests were performed on Example 1 and Comparative Example 1, respectively, to characterize the surface morphology, and the specific results are as follows:
[0079] like Figure 2 b and Figure 2 As shown in Figure d, the surface of the ITO electrode after high-energy oxygen ion pretreatment is relatively rough, with a roughness of 3.7 nm. The surface of the ITO electrode that has not been treated with high-energy oxygen ions is very smooth, as shown in Figure d. Figure 2 a and Figure 2 As shown in c, the surface roughness is 2.7nm.
[0080] Comparative Example 2
[0081] This comparative example is based on Example 1. Compared with Example 1, the only difference is that during the deposition process, high-energy oxygen ion-assisted electron beam evaporation is not used, and auxiliary deposition is not performed. The electrochromic layer deposited in this comparative example is t-WO3.
[0082] The present invention tests the thin films of Example 1 and Comparative Example 2 respectively to further illustrate the advantages of the electrochromic thin film of Example 1.
[0083] The films of Example 1 and Comparative Example 2 were tested by scanning electron microscopy and time-of-flight secondary ion mass spectrometry (ToF-SIMS) respectively, and then the interface element distribution was characterized. Figure 3 The specific results are as follows: Figure 3 The scanning electron microscope cross-sectional image of a shows that the film thickness of Q-PHI WO3 and t-WO3 is 40nm. From the three-dimensional element distribution and the profile depth ( Figure 3 bc) It can be clearly seen that In + The signal is distributed throughout the 40nm thick film. After sputtering for 1000s, In + The signal intensity increased significantly, while WO + The signal is still saturated. On the contrary, when In + When the signal reaches its saturation point, WO + The signal shows a small drop. In contrast, the conventional interface formed between ITO and t-WO3 is quite thin (about 4nm) because the In + The intensity was barely detectable even after 1000 seconds of sputtering. Moreover, upon further etching, In + and WO + The signals show almost simultaneous and opposite trends. These results provide clear evidence for the existence of a significantly extended (>40nm) longitudinal gradient interlayer between ITO and Q-PHI WO3, which is very different from the ultra-thin interlayer between Q-PHI WO3 prepared in Example 1 and traditional ITO and t-WO3 films.
[0084] Comparative Example 3
[0085] This comparative example is based on Example 3. Compared with Example 3, the only difference is that during the deposition process, high-energy oxygen ion-assisted electron beam evaporation is not used, and auxiliary deposition is not performed. The electrochromic layer deposited in this comparative example is t-WO3.
[0086] The films of Example 3 and Comparative Example 3 were tested respectively to further illustrate the advantages of the Q-PHI WO3 film of Example 3.
[0087] First, scanning electron microscope and visible light transmittance tests were performed on Example 3 and Comparative Example 3, respectively, and then the morphology and transmittance were characterized. The specific results are as follows: Cross-section SEM image ( Figure 4ab) show obvious differences in interface characteristics. The ITO / t-WO3 interface is easily identifiable, while the ITO / Q-PHI WO3 interface is obviously dense and almost fused together. Figure 4 The initial transmittance spectrum in c shows that the average transmittance of Glass / ITO / Q-PHI WO3 under visible light reaches 81.3%, which is similar to Glass / ITO / WO3 (80.4%).
[0088] Secondly, in order to evaluate the EC performance of Q-PHI WO3 and t-WO3 films, a voltage of ±0.9 V (vs. Ag / AgCl) for 20 s was applied to the films prepared in Example 3 and Comparative Example 3, and the changes in visible-near infrared transmittance were simultaneously recorded in situ to calculate their optical contrast and response time, as shown in FIG. Figure 5 As shown, Figure 5 (a) is the initial transmittance spectrum and color transmittance spectrum of Q-PHI WO3 and t-WO3 at 380-2500nm; (b) is the in-situ transmittance curve of Q-PHI WO3 and (c) t-WO3 under ±0.9V (vs.Ag / AgCl) and 20s voltage, and the inset is the digital photo of Q-PHI WO3 and t-WO3 in bleached and colored states; (d) is the in-situ transmittance curve of Q-PHI WO3 and t-WO3 after 1000 cycles under ±0.9V (vs.Ag / AgCl); (e) is the in-situ transmittance curve of Q-PHI WO3 after 10000 cycles under ±0.9V (vs.Ag / AgCl).
[0089] The test results are as follows Figure 5 a and Figure 5 As shown in b: The optical contrast (△T) of Q-PHI WO3 at 700nm reaches 82.1%, while the △T of t-WO3 film is only 78.3%. Even at a wavelength of 2500nm, the △T of Q-PHI WO3 can reach 58%, while the △T of t-WO3 is 42%. The superior broadband light modulation capability of Q-PHI WO3 film also demonstrates its potential as a smart window to regulate solar radiation. The response time is defined as the time required for a 90% change in transmittance. The coloring time and bleaching response time of Q-PHI WO3 film are only 2.4s and 1.8s, respectively. Compared with t-WO3 film, the average response time is increased by 3 times, the latter of which has a coloring and bleaching time of 4.7s and 12.1s, respectively.
[0090] Finally, in order to evaluate the electrochemical cycling stability of the WO3 thin films prepared in Example 3 and Comparative Example 3, a voltage of ±0.9 V (vs. Ag / AgCl) was applied to Q-PHI WO3 and t-WO3, and the cycle was repeated 1000 times, and the in-situ transmittance change at 700 nm was monitored. Figure 5 d and Figure 5 As shown in Figure 5e, with the increase in the number of cycles, the coloration of the t-WO3 film decreased significantly and obvious optical contrast degradation occurred. After completing 1000 consecutive electrochemical cycles, the optical contrast of the WO3 film only dropped to 41.6% of its initial value. In contrast, the coloration and optical contrast of Q-PHI WO3 increased with the increase in the number of cycles. After 1000 cycles, the optical contrast reached 106.6% of the initial value and hardly decreased before 2000 cycles. Even after 10,000 cycles, the optical contrast remained at 78.7% of the initial value. Therefore, the widened and tightly anchored quasi-planar heterointerface plays a key role in enhancing interfacial bonding and effectively releasing stress, thereby contributing to good cycling stability.
[0091] Example 5
[0092] This embodiment provides an electrochromic film with ultrafast response and high stability, which is different from the embodiment 3 in that the ion source type of high-energy ions is different. The EC device performance of the electrochromic film prepared under various ion source types is tested, and the specific ion source types and performance test results are shown in Table 1.
[0093] Table 1 Ion source types and EC performance test results of Example 5
[0094]
[0095]
[0096] Comparative Example 4
[0097] This comparative example is based on Example 2. Compared with Example 2, the only difference is that during the deposition process, high-energy argon ion-assisted electron beam evaporation is not used, and auxiliary deposition is not performed. The electrochromic layer deposited in this comparative example is t-WO3.
[0098] The scanning electron microscope was used to test the morphology of Example 2 and Comparative Example 4, and the specific results are as follows: Cross-section SEM image ( Figure 6 ) shows obvious differences in interface characteristics. The ITO / t-WO3 interface is easily identifiable, while the ITO / Q-PHI WO3 interface is obviously dense and almost fused together.
[0099] Comparative Example 5
[0100] This comparative example is based on Example 4. Compared with Example 4, the only difference is that during the deposition process, high-energy oxygen ions and argon ions are not used to assist electron beam evaporation, and no auxiliary deposition is performed. The electrochromic layer deposited in this comparative example is t-WO3.
[0101] The scanning electron microscope was used to test the morphology of Example 4 and Comparative Example 5, and the specific results are as follows: Cross-section SEM image ( Figure 7 ) shows obvious differences in interface characteristics. The ITO / t-WO3 interface is easily identifiable, while the ITO / Q-PHI WO3 interface is obviously dense and almost fused together.
[0102] Example 6
[0103] This embodiment provides an electrochromic film, which includes a substrate, an electrode and an electrochromic layer. The substrate is made of glass, the electrode is a transparent electrode, and an indium tin oxide electrode is used. The glass and indium tin oxide form a transparent electrode material. The electrochromic layer is a quasi-planar heterogeneous interface nickel oxide, and the thickness of the electrochromic layer is 200nm.
[0104] The specific preparation process includes the following steps:
[0105] (1) The glass substrate was ultrasonically cleaned with acetone, ethanol, and deionized water for 15 min in sequence, and then dried in an oven at 80°C. The cleaned glass substrate was fixed on a sample holder and placed in the electron beam cavity. When the vacuum degree in the cavity reached 2.5×10 -3 Pa, indium tin oxide was heated at 0.2 nm·s -1 The ITO was deposited on a glass substrate at a rate of 180 nm to form a transparent conductive material (glass / ITO).
[0106] (2) Then, at room temperature, high-energy oxygen ion-assisted electron beam evaporation was used to evaporate nickel oxide at a speed of 0.15 nm·s -1 The rate of evaporation deposition on the transparent conductive material was 200nm, and the deposited film thickness was 200nm to obtain a highly stable electrochromic film (ITO / Q-PHI NiO). During the deposition process, the anode voltage for generating high-energy oxygen ions was 170V, and the oxygen flux was maintained at a rate of 15sccm.
[0107] High-energy oxygen ions are generated by a Hall ion source.
[0108] Comparative Example 6
[0109] This comparative example is based on Example 6. Compared with Example 6, the difference is that Comparative Example 6 does not undergo high-energy oxygen ion pretreatment, and high-energy oxygen ion-assisted electron beam evaporation is not used during the deposition process. The remaining steps are consistent with Example 6. The electrochromic layer deposited in this comparative example is t-NiO.
[0110] The present invention performs scanning electron microscope tests on Example 6 and Comparative Example 6 respectively, and then characterizes the morphology. The specific results are as follows:
[0111] Cross-section SEM image ( Fig.11 ) show obvious differences in interface characteristics. The ITO / t-NiO interface is easily identifiable, while the ITO / Q-PHI NiO interface is obviously dense and almost fused together.
[0112] Therefore, the present invention adopts an ultrafast response and high stability electrochromic film and its preparation method using the above structure, which is different from the traditional planar heterogeneous interface and nanostructured heterogeneous interface. With the help of high-energy oxygen, argon or nitrogen ions, it significantly broadens the nanoscale interface contact and unique longitudinal gradient distribution characteristics. The unique Q-PHI can generate a strong built-in electric field and strong interface bonding, which greatly promotes the transport kinetics of electrons and ions and enhances the Li + The surface adsorption of the electrochromic film was reduced and the stress during continuous electrochemical cycling was effectively released. Therefore, the electrochromic film prepared by the present invention overcomes the trade-off between high stability and ultrafast switching performance and exhibits remarkable overall EC performance, including high optical contrast, ultrafast switching speed and excellent stability.
[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A high-stability electrochromic film, characterized in that: The electrochromic film comprises a conductive material and an electrochromic layer. The electrochromic layer is a quasi-planar heterogeneous interface metal oxide. The thickness of the electrochromic layer is 10 to 1000 nm.
2. The high-stability electrochromic film according to claim 1, characterized in that: The metal oxide is one or more of WO3, MoO3, NiO and TiO2.
3. A method for preparing a high-stability electrochromic film according to any one of claims 1 to 2, characterized in that: The following steps are involved: The conductive material is fixed on a sample holder and placed in an electron beam cavity, and the conductive material is pretreated. Then, high-energy ion-assisted electron beam evaporation is used to evaporate and deposit metal oxide on the conductive material to obtain an electrochromic film.
4. The method for preparing a high-stability electrochromic film according to claim 3, characterized in that: The vacuum degree in the electron beam cavity is 1×10 -4 Pa~5×10 -3 Pa, uses high-energy ions to bombard the surface of conductive materials for pretreatment.
5. The method for preparing a high-stability electrochromic film according to claim 3, characterized in that: At 20-300°C, the metal oxide is heated to 0.1-1 nm·s -1 The rate of evaporation deposition is 200 ℃ and 200 ℃ on the pretreated conductive material.
6. The method for preparing a high-stability electrochromic film according to claim 3, characterized in that: The high-energy ions are one or more of oxygen ions, argon ions and nitrogen ions.
7. The method for preparing a high-stability electrochromic film according to claim 6, characterized in that: The acceleration voltage of high-energy ions is 130~300V.
8. An electrochromic device, characterized in that: The electrochromic device comprises an electrochromic film obtained by the preparation method of claims 3 to 6, an electrolyte layer, a conductive layer and a protective layer.
9. An electrochromic device according to claim 8, characterized in that: The electrolyte layer is a gel electrolyte. The preparation method of the gel electrolyte is as follows: PMMA and PC are mixed evenly, placed in an oven at 60-80°C for heating and swelling for 15-20 hours to obtain a transparent gel, and then LiClO4 and acetonitrile are added, followed by stirring on a magnetic stirrer at 60-80°C for 10-15 hours to make the electrolyte salt evenly distributed in the transparent gel to finally form a gel electrolyte.
10. An electrochromic device according to claim 9, characterized in that: The molecular weight of PMMA is 100,000 to 150,000, and the mass ratio of PMMA, PC, LiClO4 and acetonitrile is (3 to 5): (8 to 12): (1 to 2): (5 to 10).
Citation Information
Patent Citations
Heterogeneous interface material based on oxygen plasma, preparation method and application
CN115763736A
Method for insulation and waterproof using aluminum sheets and structure therefor
KR102909925B1
Stacked bulk heterojunction solar cells for broadband and tailorable spectral coverage
US20210050540A1
Electrochromic window with high reflectivity modulation
US6094292A